2010
DOI: 10.1097/01.aoa.0000370534.89790.da
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Outcomes After Elective Cesarean Delivery

Abstract: P regnancy can trigger the first episode of depression in a women or a recurrence of depression in those women with a prior history of the disorder. The prevalence of depression during pregnancy is estimated at 8% to 51%. The wide range in cited prevalence can be due to variations in the criteria used to diagnose depression and the timing and types of assessments used for evaluation of the disorder. This study evaluated the time to onset, duration, and risk factors for major and minor depression in pregnant wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 8 publications
5
62
0
7
Order By: Relevance
“…Kamath et al in a study of 672 women with one prior CS, reported that neonates born by CS had more NICU admissions compared to VBAC group (p=0.025). 14 In was observed that infection (4%) at the time of previous CS have decreased rate of VBAC in subsequent trial of labour which is consistent with the study by Dodd et al 15 The present study had limitation of being small in sample size; a large randomized trial is required to confirm the present study findings.…”
Section: 13supporting
confidence: 90%
“…Kamath et al in a study of 672 women with one prior CS, reported that neonates born by CS had more NICU admissions compared to VBAC group (p=0.025). 14 In was observed that infection (4%) at the time of previous CS have decreased rate of VBAC in subsequent trial of labour which is consistent with the study by Dodd et al 15 The present study had limitation of being small in sample size; a large randomized trial is required to confirm the present study findings.…”
Section: 13supporting
confidence: 90%
“…Other studies have used repeat cesarean delivery as a proxy for elective cesarean delivery, which is not comparable with a primary cesarean delivery without labor. 17,18 In many cases, information on parity and maternal morbidities was not available, making it difficult to determine what effects were due to parity or comorbidity and what were actually due to planned route of delivery. 13 Another strength of this study is the use of large, universitybased databases that include detailed data on demographic, labor and delivery and postnatal information over a 10-year time span that is populated and maintained by clinical research nurses.…”
Section: Discussionmentioning
confidence: 99%
“…The baby's lungs mature, and he puts on a protective layer of fat. Every day makes a difference in how mature the baby is and how well he is able to make the transition to life outside the womb (Kamath, Todd, Glazner, Lezotte, & Lynch, 2009).…”
Section: Evidence-based Birth Practices Make Birth Healthier and Safementioning
confidence: 99%